THE ENVIRONMENTAL DRIVERS BEHIND THE DEVELOPMENT OF THE VICTORIAN TEXTILE FACTORY - Suci Farahdilla (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2021)
Textile industry in the nineteenth century of the British empire was one of the milestone industries which center around cotton mills. The development of this industry attracted many people who wished to increase their life’ standard to migrate to area near the factories located in order to work there. As much as giving revenue for the country, these factories also gave impact to the environment as well as people living and working in it. There were three things behind the environmental impact during the Victorian era of textile industry, fire hazard, mills’ poor conditions and factory bill. Flammable materials, like raw cotton which mainly used in this industry, and high temperature room caused the factories engulfed in fire. The lacked protection from fire of the factories’ construction then led to a new building method being introduced and applied called the “Fireproof Construction”. Poor health condition of the workers who worked in high humidity and temperature of cotton mills brought a creation of factory bill (Factory Act) being passed. However, the act that was supposed to act as a regulation for factories owners to offer their worker a much more suitable place to work was hardly fully implied during this time. The writer used literature review method in collecting data. This article therefore intended to deliver the reader about the environment situation in the cotton factories while also giving the idea on how hardly an ideal comfort was achieved.